2010
DOI: 10.1074/jbc.m109.058750
|View full text |Cite
|
Sign up to set email alerts
|

The Carboxyl-terminal Domain of Connexin43 Is a Negative Modulator of Neuronal Differentiation

Abstract: Connexin43 (Cx43) is widely expressed in embryonic brain, and its expression becomes restricted mainly to astrocytes as the central nervous system matures. Recent studies have indicated that Cx43 plays important, nonchannel, roles during central nervous system development by affecting neuronal cell migration. Here, we evaluated the effects of Cx43 on neuronal differentiation. For that we used an in vitro model of neural cell development (neurospheres) to evaluate, through immunocytochemistry, electrophysiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 51 publications
2
40
1
1
Order By: Relevance
“…Recently, studies using Cx43cKO and Cx43k258stop mice have indicated that the C terminus is required for cortical neuronal migration (30). In addition, independent regulation of the gap junction channel or C-terminal domain in neurite outgrowth (31,32) and cellular motility (33)(34)(35)(36)(37) have been demonstrated in various cell types, indicating that they may affect the neocortical development (38).…”
mentioning
confidence: 99%
“…Recently, studies using Cx43cKO and Cx43k258stop mice have indicated that the C terminus is required for cortical neuronal migration (30). In addition, independent regulation of the gap junction channel or C-terminal domain in neurite outgrowth (31,32) and cellular motility (33)(34)(35)(36)(37) have been demonstrated in various cell types, indicating that they may affect the neocortical development (38).…”
mentioning
confidence: 99%
“…Cx43, besides conveying channel forming properties, has also been described as being involved in the regulation of additional biological functions, such as control of cell growth, cell survival, and differentiation (5,6); migration of neural precursor and glioma cells (7)(8)(9); and neuroprotection after hypoxic stress (10). An inverse relationship exists between Cx43 expression and cell growth (11,12), and a carboxyl-terminal domain was found to be as effective as full-length Cx43 in suppressing cell growth in a variety of cell lines (13)(14)(15).…”
mentioning
confidence: 99%
“…Several independent studies have highlighted an important role for Cxs, Cx43 in particular, in regulating NPC proliferation as well as the migration and differentiation of young excitatory neurons in the embryonic cerebral cortex. In Cx43-null brains of mice, the thickness of the CP was found to be reduced and this was accompanied by an impairment in lamination of the neocortex and accumulation of neurons in the IZ sublayer (E18, E21) [93,164,165] or the VZ/SVZ (E16) [166]. These effects may be caused by a defective migration [93,164] or by the induction of premature neuronal differentiation [166].…”
Section: General Concepts Of Connexin and Pannexin Signalingmentioning
confidence: 99%
“…In Cx43-null brains of mice, the thickness of the CP was found to be reduced and this was accompanied by an impairment in lamination of the neocortex and accumulation of neurons in the IZ sublayer (E18, E21) [93,164,165] or the VZ/SVZ (E16) [166]. These effects may be caused by a defective migration [93,164] or by the induction of premature neuronal differentiation [166]. The role of neuronal Cx43 in cortical lamination was recently confirmed by the use of neuron-specific, conditional Cx43 KO mice.…”
Section: General Concepts Of Connexin and Pannexin Signalingmentioning
confidence: 99%